2010
DOI: 10.1002/jbm.a.32651
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of dexamethasone from subcutaneously‐implanted biosensors in pigs: Localized anti‐inflammatory benefit without systemic effects

Abstract: Chronically implanted biosensors typically lose sensitivity 1-2 months after implantation, due in large part to the development of a collagen-rich capsule that prevents analytes of interest from reaching the biosensor. Corticosteroids are likely candidates for reducing collagen deposition but these compounds have many serious side effects when given over a prolonged period. One method of assessing whether or not locally released corticosteroids have a systemic effect is to measure cortisol concentrations in ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 29 publications
(37 reference statements)
3
28
0
Order By: Relevance
“…Similar results were found in reports by Klueh et al where the inflammation around implanted sensor probes was diminished when Dex was locally delivered [20]. Moreover, several studies have reported on a decrease in macrophage density as a function of Dex release from indwelling microdialysis probes and osmotic pumps [3638]. …”
Section: Discussionsupporting
confidence: 86%
“…Similar results were found in reports by Klueh et al where the inflammation around implanted sensor probes was diminished when Dex was locally delivered [20]. Moreover, several studies have reported on a decrease in macrophage density as a function of Dex release from indwelling microdialysis probes and osmotic pumps [3638]. …”
Section: Discussionsupporting
confidence: 86%
“…Prior studies have shown that local Dex delivery is able to improve sensor performance past the “break-in period” by decreasing leukocyte migration and inflammation at the implant site (19, 22, 23, 25, 38). However, when Dex is delivered over the long-term (>1 month) the drug can act as an angiostatic agent leading to reduced microvessel density, vasodilation, and increased vascular permeability at the implant site.…”
Section: Discussionmentioning
confidence: 99%
“…Attenuation of inflammation contends that the benefits of minimizing the deleterious effects of acute inflammation on sensor function outweigh the potential advantages of engineering the tissue response. One strategy for the attenuation of acute inflammation involves the local release of anti-inflammatory mediators such as nitric oxide, non-steroidal anti-inflammatory drugs, and glucocorticoids (17-19). …”
Section: Introductionmentioning
confidence: 99%
“…There are numerous examples of the use of dexamethasone to reduce inflammation in a biomaterials context [14, 2831]. However, the endpoint analyses in these studies are frequently histological analysis of H&E and Masson’s Trichrome stains.…”
Section: Introductionmentioning
confidence: 99%